THE EFFECT OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL ON THE CRITICAL THINKING SKILLS OF FOURTH-GRADE ELEMENTARY STUDENTS - Ainun; Sri Suryaningsih; Jessy Parmawati Atmaja (Universitas Majalengka, 2025)
The background of this research stems from the importance of mastering critical thinking skills from the elementary school level, especially in the development of science and technology. The purpose of this study is to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on students’ critical thinking skills in IPAS learning for fourth-grade students at SDN Inpres Leu. This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects were all 36 fourth-grade students of SDN Inpres Leu, consisting of 18 students in the experimental class and 18 students in the control class. The instrument used was an open-ended test designed to measure students’ critical thinking skills. The data analysis technique was carried out through several stages, including prerequisite tests such as normality and homogeneity tests, followed by hypothesis testing using the independent sample t-test. The results of the analysis showed a significance value (2-tailed) of 0.000 < 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Thus, there is a significant effect of using the CIRC learning model on improving the critical thinking skills of fourth-grade students. These findings suggest that the implementation of the CIRC learning model can serve as an innovative instructional strategy to enhance the quality of the teaching and learning process, particularly in IPAS learning at the elementary school level.